2018
DOI: 10.18356/b18dd784-en
|View full text |Cite
|
Sign up to set email alerts
|

Contract farming, agriculture productivity and poverty reduction: Evidence from tea estates in Viet Nam

Abstract: Interest in contract farming is increasing because of its potential as an alternative channel for linking producers to international markets. However, there is limited knowledge on contract farming of tea production in Viet Nam, especially in more inaccessible provinces where tea production plays an important role in generating employment, improving livelihood and reducing poverty. In the present paper, the impact of contract farming on productivity is reviewed in Pho Tho province, a major tea production area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…However, an increase in log of fertilizer, labour, seeds, and chemical by one-unit augmented tobacco yield by 47, 43, 16, and 9%, respectively. These results are stable across the three SFA models and findings by Nguyen et al [ 47 ].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, an increase in log of fertilizer, labour, seeds, and chemical by one-unit augmented tobacco yield by 47, 43, 16, and 9%, respectively. These results are stable across the three SFA models and findings by Nguyen et al [ 47 ].…”
Section: Resultssupporting
confidence: 78%
“…Participation in CFA is not a random process [ 47 ], depending on the attributes of contractors and farmers. Contracted smallholder farmers usually have unique attributes which results in CFA self-selection, namely, farm size, farmers' club membership, tobacco experience, and curing facilities [ 31 ].…”
Section: Propensity Score Matching Techniquementioning
confidence: 99%
“…Nguyen et al [12] revealed that contract farming is supported to achieve SDG1 in Vietnam. Implementing contract farming helps to improve productivity.…”
Section: Sustainable Development Goals (Sdgs) and Tea Plantation Comp...mentioning
confidence: 99%